Self-assembly of Keggin-type U(vi)-containing tungstophosphates with a sandwich structure: an efficient catalyst for the synthesis of sulfonyl pyrazoles. Issue 21 (8th September 2021) - Yang, Guo-Ping; Zhang, Xing-Lei; Liu, Yu-Feng; Zhang, Dong-Di; Li, Ke; Hu, Chang-Wen
Abstract : Two Keggin-type U(vi )-containing tungstophosphates with sandwich structure were synthesized and characterized. Compound 1 presents excellent catalytic activity towards the condensation cyclization of sulfonyl hydrazines with 1, 3-diketones to synthesize sulfonyl pyrazoles. Abstract : The reaction of UO2 (OAc)2 and Na9 [A-PW9 O34 ] in solution with different pH values leads to the formation of two Keggin-type sandwich polyoxometalates, namely Na11 H(H2 O)31 [Na(UO2 )(A-PW9 O34 )]2 ·7H2 O (1 ) and Na12 (H2 O)29 [Na(UO2 )(A-PW9 O34 )]2 ·7H2 O (2 ), which have been characterized by single-crystal X-ray diffraction, FT-IR spectroscopy, and PXRD techniques. Compounds 1 and 2 crystallize in similar conditions with different pH values and show similar sandwich crystal structures except that one extra Na(i ) ion acts as a bridging linker in compound 2 than in 1 . It is notable that 1 exhibits excellent catalytic activity for the synthesis of sulfonyl pyrazoles via the condensation and cyclization reaction of sulfonyl hydrazides with 1, 3-diketones, and the yield of the desired product is up to 99%. This is the first report to investigate the catalytic properties of U-containing polyoxometalates.